Body shots : early cinema's incarnations - Auerbach, Jonathan, 1954- (University of California Press, 2007)
Argues that it was the human form in motion that most profoundly shaped early cinema. Situating his discussion in a political and historical context, the author begins his analysis with films that reveal striking anxieties and preoccupations about persons on public display. It also considers twentieth-century American incarnation of cinema itself.
Keywords: Human body in motion pictures.; Silent films -- History and criticism.; Corps humain au cinéma.; Films muets -- Histoire et critique.; PERFORMING ARTS -- Film & Video -- Reference.; PERFORMING ARTS -- Film & Video -- General.; Human body in motion pictures; Silent films; 19th century american film history.; 20th century american film history.; american film.; american fireman.; bodies in public.; bodies in space.; cinema of attractions.; cinema production.; cinema.; corporeal movement.; early cinema.; film history.; film narrative.; film studies.; film.; human form in motion.; movie history.; movie studies.; movies.; persons on public display.; presidential candidate.; self consciousness.; visual art.; visual spectacle.; william mckinley.; Criticism, interpretation, etc.